Effect of soil moisture and organic matter levels on plantain root reaction to Radopholus similis - Rotimi, M.; Speijer, P.; Waele, D. de (2004)
The influence of some edaphic factors (soil moisture and organic matter) on plantain susceptibility to Radopholus similis was studied on cultivar Agbagba in a shade house. Densities of R. similis increased with increasing soil moisture level and were highest at field capacity revealing that at the peak of the rainy season, high densities could be expected under plantain cultivar Agbagba under field conditions. Slow drying out of soil strongly impaired root health. The implication of this is that although densities of R. similis might be low in the dry season, heavy damage is axpected on cultivar Agbagba if R. similis is present. Nematode densities recovered decreased with increasing organic matter level. A medium that supported high densities of R. similisalso allowed a high degree of necrosis, while dead root incidence increased with increasing organic matter level. This indicates that limiting food availability could have been resposible for the nematode population decrease. Highest root weight was obtained in a medium that supported low densities of R. similis, suggesting that low nematode pressure could enhance root growth of Agbagba.